Profana: the mysteries in Greek and Roman literature - Liu, C (2023)
This thesis explores the relationship between the Mysteries and Greco-Roman literature from the 6th century BCE to the 1st century CE. The study of the mystery cults of ancient Greece and Rome--the Eleusinian mysteries, Bacchic cult, and the Orphic tradition—has largely been confined to the historical reconstruction of their secret rites, exclusive communities, doctrines, and experiences; current scholarship has treated ancient literature, both poetic and philosophic texts, merely as documentary sources on the mysteries and mined them for data. I reverse this approach, deploying what we know about the mysteries to identify and understand the function of such religious experiences within their literary contexts. I use the mysteries as a lens to explore questions of knowledge creation and exchange, and knowledge communities, in literature from Pindar to Plato to Ovid. The few existing studies on the influence of the mysteries on literature have been confined to single authors or works, largely ignoring the interactions and parallels in cultic references between texts; indeed, none has addressed mystery cults in relation to Hellenistic and Roman poetry beyond Virgil and Lucretius. My research addresses these gaps, bringing a variety of poetic and philosophical texts into conversation to explore the valence of mystery cults in ancient literary and philosophical discourse.